Mailed Letter Versus Phone Call to Increase Diabetic-Related Retinopathy Screening Engagement by Patients in a Team-Based Primary Care Practice: Prospective, Single-Masked, Randomized Trial - Vess Stamenova; Megan Nguyen; Nike Onabajo; Rebecca Merritt; Olivera Sutakovic; Kathryn Mossman; Ivy Wong; Lori Ives-Baine; R Sacha Bhatia; Michael H Brent; Onil Bhattacharyya (JMIR Publications, 2023)
BackgroundVision loss from diabetic-related retinopathy (DR) is preventable through regular screening. ObjectiveThe purpose of this study was to test different patient engagement approaches to expand a teleophthalmology program at a primary care clinic in the city of Toronto, Canada. MethodsA teleophthalmology program was set up in a large, urban, academic, team-based primary care practice. Patients older than 18 years with type 1 or type 2 diabetes were randomized to one of the following 4 engagement strategies: phone call, mail, mail plus phone call, or usual care. Outreach was conducted by administrative staff within the clinic. The primary outcome was booking an appointment for DR screening. ResultsA total of 23 patients in the phone, 28 in the mail, 32 in the mail plus phone call, and 27 in the control (usual care) group were included in the analysis. After the intervention and after excluding patients who said they were screened, 88% (15/17) of patients in the phone, 11% (2/18) in the mail, and 100% (21/21) in the mail and phone group booked an appointment with the teleophthalmology program compared to 0% (0/12) in the control group. Phoning patients positively predicted patients booking a teleophthalmology appointment (P<.001), whereas mailing a letter had no effect. ConclusionsPatient engagement to book DR screening via teleophthalmology in an urban, academic, team-based primary care practice using telephone calls was much more effective than patient engagement using letters or usual care. Practices that have access to a local DR screening program and have resources for such engagement strategies should consider using them as a means to improve their DR screening rates. Trial RegistrationClinicalTrials.gov NCT03927859; https://clinicaltrials.gov/ct2/show/NCT03927859